2020
DOI: 10.21203/rs.3.rs-34001/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammatory olfactory neuropathy in two patients with Covid-19 

Abstract: Coronavirus disease 2019 (Covid-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged as a public health emergency recently, leading to fatal respiratory failure in a number of patients. The clinical manifestation of Covid-19 is manifold, cardio-respiratory symptoms and multiorgan failure being the most critical. Anosmia was reported to be an early symptom in a significant number of Covid-19 patients and is frequently the only symptom without underlying nasal congestion. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In an autopsy study of two patients that died of COVID-19 infection (one had anosmia as early feature), authors found inflammation and axonal damage in the olfactory bulb explaining the olfactory symptoms [94]. In both cases, olfactory striae were normal.…”
Section: Olfactory and Gustatory Dysfunctionmentioning
confidence: 97%
See 1 more Smart Citation
“…In an autopsy study of two patients that died of COVID-19 infection (one had anosmia as early feature), authors found inflammation and axonal damage in the olfactory bulb explaining the olfactory symptoms [94]. In both cases, olfactory striae were normal.…”
Section: Olfactory and Gustatory Dysfunctionmentioning
confidence: 97%
“…Since SARS-CoV-2 is a respiratory virus, the virus particles have been shown in the CD 68 macrophages in the biopsy of nasal tissues from patients presenting with COVID-19related olfactory dysfunction [96]. Patients with olfactory dysfunction may have inflammation and edema of olfactory bulb [94,95]. In animal studies, it has been shown that coronavirus may utilize olfactory pathway to gain entry into central nervous system [101].…”
Section: Patho-mechanism Of Nervous Tissue Involvementmentioning
confidence: 99%
“…Histopathologic examination of the brain confirmed leukocytic infiltration and thrombosis. The study could not confirm whether the inflammation on the neuronal tissue was a direct effect of the infection or otherwise [10]. In view of the COVID-19 disease complexity and due to the unavailability of specific therapeutic drugs, careful management of COVID-19 patients assumes increased significance.…”
mentioning
confidence: 93%
“…Following growing anecdotal evidence suggesting an increasing incidence of cases of anosmia during the current pandemic, on 18th May the UK government added anosmia and ageusia to the list of symptoms of coronavirus infection. 1,2 There is now considerable evidence that a new onset of altered sense of smell or taste is related to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. 3 An objective evaluation of olfactory and gustatory function in the first days of infection is almost impossible, as affected individuals are generally in home quarantine.…”
mentioning
confidence: 99%